Analyzing Mass Attitudes Toward the International Court of Justice. Issue 2 (22nd January 2021) - Justwan, Florian; Fisher, Sarah K; Kerr, Ashley; Berejikian, Jeffrey D
Abstract: This paper analyzes public attitudes about the International Court of Justice (ICJ). We explore two questions: (1) Why are some people in favor of submitting their country's disputes to the ICJ while others are opposed? (2) How can we explain variations in public support for compliance with a costly ICJ ruling? We argue that individual-level attitudes about both issues are driven by different psychological dynamics. While we expect that cost–benefit calculations and cosmopolitan social identity will affect attitudes in both contexts, people's views on compliance should also be shaped by their level of social dominance orientation (SDO). Our statistical analysis is based on original survey data, collected in Belize in April 2019. We obtain three main findings. First, people's ex ante beliefs about the costs of an ICJ ruling have tangible effects on attitudes toward ICJ adjudication. As predicted, higher expected costs lead to decreased support for adjudication. Second, cosmopolitanism is positively associated with support for adjudication, but it has no effect on attitudes about compliance with international court rulings. Third, high-SDO respondents are less likely to favor the implementation of a costly ICJ verdict. However, SDO only reduces support for compliance in individuals with narrow social identity attachments.